2013
DOI: 10.1002/jgrd.50206
|View full text |Cite
|
Sign up to set email alerts
|

Forced Sahel rainfall trends in the CMIP5 archive

Abstract: [1] The simulations of the fifth Coupled Models Intercomparison Project (CMIP5) strengthen previous assessments of a substantial role of anthropogenic emissions in driving precipitation changes in the Sahel, the semiarid region at the southern edge of the Sahara. Historical simulations can capture the magnitude of the centennial Sahel drying over the span of the 20th century and confirm that anthropogenic forcings have contributed substantially to it. Yet, the models do not reproduce the amplitude of observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
228
0
3

Year Published

2014
2014
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(272 citation statements)
references
References 61 publications
41
228
0
3
Order By: Relevance
“…In any case, knowledge of the interannual to decadal variability in the monsoon circulation is still quite limited (Afiesimama et al, 2006;Maloney and Shaman, 2008). The simulations of the fifth Coupled Model Intercomparison Project (CMIP5) confirm results from previous generations of models attributing a substantial role of anthropogenic emissions in driving precipitation changes in the Sahel (Biasutti, 2013). They also suggest that in a warming world, the WAM season may be shifted toward the end of the year, as they report a drying spring and wetting fall.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…In any case, knowledge of the interannual to decadal variability in the monsoon circulation is still quite limited (Afiesimama et al, 2006;Maloney and Shaman, 2008). The simulations of the fifth Coupled Model Intercomparison Project (CMIP5) confirm results from previous generations of models attributing a substantial role of anthropogenic emissions in driving precipitation changes in the Sahel (Biasutti, 2013). They also suggest that in a warming world, the WAM season may be shifted toward the end of the year, as they report a drying spring and wetting fall.…”
Section: Introductionsupporting
confidence: 57%
“…Fontaine and Janicot (1996) later simplified this classification as they found that the western and continental Sahel rainfall anomalies were of the same sign for the majority of stations they analyzed. More recently, east-west contrasts have also been noted at decadal timescales (Dieppois et al, 2013) as well as at longer timescales, related to the long-term trends in response to climatic forcing (e.g., Lebel et al, 2009;Monerie et al, 2012;Biasutti, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, as shown in the future projection from 'gfdl-cm2.1' and 'miroc3_2_medres' in CMIP3 (refs 1,2), two CMIP5 models from the same family, GFDL-ESM2M and MIROC-ESM, still project a substantially dryer and wetter Sahel, respectively, under a medium future emission scenario (Representative Concentration Pathways 4.5; RCP4.5). A recent study using the strongest radiatively forced future scenario for CMIP5 also supports the model variability of future Sahel rainfall trends 16 . We cannot ignore those two extreme simulations because either the drying or wetting of the Sahel is a physically plausible response to increased radiative forcing, and these two models provide relatively accurate simulations of the West African summer rainfall in the historical period 3 .…”
Section: Statistical Analysis Of Multi-model Outputs In Cmip5mentioning
confidence: 52%
“…A second significant increase is observed at the end of the rainy season (end of Augustbeginning of September). Biasutti (2013) found modifications in the seasonal cycle of the Sahelian precipitation in the twentyfirst century, as a response to greenhouse gas forcing, observing a negative (positive) trend of precipitation in early (late) monsoonal season, whereas Cook and Vizy (2015) found no difference. The SHL intensity trends observed in both early and late monsoonal season suggest a significant modulation of the global forcing by the SHL regional signal.…”
Section: Temporal and Spatial Variabilities Of The Temperature Trendsmentioning
confidence: 97%